THE INFLUENCE OF CREATOR CONTENT ON BRAND IMAGE ON TIKTOK SAMPO KEMAIU - Safitri, Dian Ayu; Mandasari, Virginia (International Journal of Multidisciplinary Research and Literature, 2024)
This research aims to understand the impact of creator content on brand image on the TikTok social media platform, especially in the context of the product "Sampo Kemaiu". By using a qualitative approach and descriptive research design, this research applies postpositivist philosophy and interview techniques as data collection methodology. The research results show that content creators have a significant role in shaping brand image, especially when the content meets brand criteria and is able to increase interaction with TikTok users. Creativity, quality and communication skills of content creators are important factors in successful marketing collaborations. In addition, factors such as consumer perception of the product, assessment of quality and price, and evaluation of product location also influence the overall brand image. This study provides comprehensive insight into the complexity of factors influencing brand image on TikTok, providing important contributions to marketing practitioners and research in this area